(untitled) (Sociologisk Forskning, 2025)
This article presents an integrated interpretation of Max Weber’s view on the role of values in scientific inquiry by linking four social categories – personality, vocation, Bildung, and ethics of responsibility – with four epistemological concepts: historical interest, value relevance, cultural meaning, and value interpretation. Previous interpretations have mostly focused on epistemological and logical aspects of value interference in science, leaving the relationship between Weber’s categories – and the mechanisms through which values shape scientific problem selection – underexplored. Drawing on the case of familial homicides, we argue that researchers integrate their values into the research process through a three-stage model. We trace the origins of Weber’s concept of value interpretation to perspectivism and Nietzsche’s notion of a “battle of values.” By examining the historical development of the concepts of interest and value relevance – particularly in relation to Kant’s theory of reason – we propose a revised reading of the epistemological foundations of Weber’s approach. Finally, we analyze the methodological implications of personality, vocation, Bildung, and responsibility ethics in Weber’s social theory, highlighting their significance for understanding how values are embedded in the selection and framing of scientific problems.